Comprehensive multi-omics analysis showed that CDC6 is a potential prognostic and immunotherapy biomarker for multiple cancer types including HCC - Chenxuan Li; En-di Zhang; Rui Yu; Bo Yuan; Yunxin Yang; Zhong Zeng; Hanfei Huang (Translational Oncology)
Background: Cell division cycle 6 (CDC6) is a member of the AAA+ ATPase family and has chaperone-like activity. Many studies have shown that CDC6 plays an important role in cancer development and progression. Methods: Explored CDC6 mRNA and protein expression in normal human tissues and tumors using TCGA, GTEx, and HPA. The role of CDC6 in cancer was analyzed using multiple web platforms and software, including R, cBioPortal, UALCAN, SangerBox and others. Finally, CCK-8, EdU assays and Transwell assays were used to verify the effects of CDC6 knockdown on HCC cell proliferation, migration, and invasion. Results: CDC6 expression was upregulated in most cancers and was associated with poorer prognosis. RNA methylation may play an important role in CDC6 epigenetic modification. CDC6 was significantly positively associated with CD4+ Th2 cells and MDSC in a variety of tumors. Furthermore, immunomodulatory genes are strongly associated with CDC6 expression in most tumor types. CDC6 has higher predictive value than B. Clonality and TMB, and its expression is significantly positively correlated with TMB/MSI and DNAss/RNAss, and is closely related to cell cycle events. Down-regulation of CDC6 can inhibit proliferation, migration and invasion of HCC cells. Conclusions: CDC6 is associated with the occurrence and progression of multiple cancer types by regulating the cell cycle. It holds promise as a diagnostic and prognostic biomarker for cancer, and offers potential in immunomodulatory and targeted therapies.